Characterization of the Streptomyces coelicolor Glycoproteome Reveals Glycoproteins Important for Cell Wall Biogenesis - Tessa Keenan (American Society for Microbiology, 2019)
ABSTRACT The physiological role of protein O-glycosylation in prokaryotes is poorly understood due to our limited knowledge of the extent of their glycoproteomes. In Actinobacteria, defects in protein O-mannosyl transferase (Pmt)-mediated protein O-glycosylation have been shown to significantly retard growth (Mycobacterium tuberculosis and Corynebacterium glutamicum) or result in increased sensitivities to cell wall-targeting antibiotics (Streptomyces coelicolor), suggesting that protein O-glycosylation has an important role in cell physiology. Only a single glycoprotein (SCO4142, or PstS) has been identified to date in S. coelicolor. Combining biochemical and mass spectrometry-based approaches, we have isolated and characterized the membrane glycoproteome in S. coelicolor. A total of ninety-five high-confidence glycopeptides were identified which mapped to thirty-seven new S. coelicolor glycoproteins and a deeper understanding of glycosylation sites in PstS. Glycosylation sites were found to be modified with up to three hexose residues, consistent with what has been observed previously in other Actinobacteria. S. coelicolor glycoproteins have diverse roles and functions, including solute binding, polysaccharide hydrolases, ABC transporters, and cell wall biosynthesis, the latter being of potential relevance to the antibiotic-sensitive phenotype of pmt mutants. Null mutants in genes encoding a putative d-Ala-d-Ala carboxypeptidase (SCO4847) and an l,d-transpeptidase (SCO4934) were hypersensitive to cell wall-targeting antibiotics. Additionally, the sco4847 mutants displayed an increased susceptibility to lysozyme treatment. These findings strongly suggest that both glycoproteins are required for maintaining cell wall integrity and that glycosylation could be affecting enzyme function. IMPORTANCE In prokaryotes, the role of protein glycosylation is poorly understood due to our limited understanding of their glycoproteomes. In some Actinobacteria, defects in protein O-glycosylation have been shown to retard growth and result in hypersensitivity to cell wall-targeting antibiotics, suggesting that this modification is important for maintaining cell wall structure. Here, we have characterized the glycoproteome in Streptomyces coelicolor and shown that glycoproteins have diverse roles, including those related to solute binding, ABC transporters, and cell wall biosynthesis. We have generated mutants encoding two putative cell wall-active glycoproteins and shown them to be hypersensitive to cell wall-targeting antibiotics. These findings strongly suggest that both glycoproteins are required for maintaining cell wall integrity and that glycosylation affects enzyme function.